Enteric coating of granules containing the probiotic Lactobacillus acidophilus - Pyar Hassan; Peh Kok-Khiang (Acta Pharmaceutica)
In the present study, a capsule formulation composed of enteric coated granules of Lactobacillus acidophilus ATCC 4962 was developed using Eudragit L30D-55 as enteric polymer. Optimization of the capsule formulation was achieved with a maximum viable cell count after 2 h of incubation in acid medium and disintegration time of 1 h in buffer pH 6.8. The amount of Eudragit L30D-55 in the capsules correlated with gastric juice resistance. The best protective qualities against artificial gastric juice were observed when capsules were prepared from granules composed of L. acidophilus, corn starch, lactose monohydrate, polyvinylpyrrolidone and coated with 12.5 % (m/V) of Eudragit L30D-55. Capsule formulation of L. acidophilus in edible broth medium suspension serves as a cheap alternative to the expensive freeze-drying procedure for preparing L. acidophilus. In addition, the enteric coating using Eudragit L30D-55 could protect probiotics from the acidic gastric environment and enhance the bioactivity of probiotics along with replacement of pathogenic microbes in human intestine